Deploy MEAN Stack app on Azure Cloud with CICD Pipeline - Pandey, Ranjan, presenter (Packt Publishing Ltd., 2022)
Be a part of a practical and step-by-step course based on full-stack application (MEAN) deployment on Azure Cloud with CICD Pipeline using Azure DevOps and other cloud services.